Growth Characteristics and Fruit Quality of Chili Pepper under Higher Electrical Conductivity of Nutrient Solution Induced by Various Salts - Ahmadi, Mohammad; Souri, Mohammad Kazem (AGRIVITA, Journal of Agricultural Science, 2020)
Salinity as a global challenge is a very complex issue in agricultural food production. In this study, the growth characteristics of chili pepper (Capsicum annuum var. crusader) were evaluated under higher Electrical Conductivity (EC) (5 dS/m) induced by NaCl, KCl, Kâ‚‚SOâ‚„ or â€œAll Nutrientsâ€ of Hoagland nutrient solution. The standard Hoagland solution (with EC 1.8 dS/m) was used as the control. The results showed that EC5 induced by NaCl resulted in the most negative effects on growth, yield and fruit quality parameters. Application of KCl (to induce EC5) also resulted in some reduction in growth parameters. However, application of Kâ‚‚SOâ‚„ and particularly â€œAll Nutrientsâ€ (to induce EC5) resulted in better growth characteristics compared to plants treated with NaCl or KCl salts. There was a significant reduction in growth and fruit quality traits including plant height, leaf SPAD value, fresh and dry weights of shoots and roots, fruit fresh yield, fruit total soluble solids (TSS) and vitamin C content by NaCl and to lesser extent by KCl. However, there was no significant reduction in these traits by â€œAll Nutrientsâ€ and for some traits by Kâ‚‚SOâ‚„ application compared to control plants.